2021
DOI: 10.6007/ijarafms/v11-i1/8851
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Supply Chain Integration Towards Supply Chain Performance in Manufacturing Firms

Abstract: Supply chain integration are network links of an organisation or firm with its business partners such as customers and suppliers by integrating their relationships, functions and processes. Meanwhile as supply chains continue to replace individual firms as the economic engine for creating value during the twenty-first century, understanding the supply chain performance becomes increasingly important for both practitioners and researchers. Previous studies have addressed supply chain integration and supply chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…They defined SCP as the benefits an organization gets from supply chain participation of course not limited to efficiency improvement, price reduction, as well as enhancement in cycle time (Yu, 2015). Asnordin et al (2021) observed that previous research has actually confirmed that an effective and reliable supply chain supplies top quality products on time and in the right amounts. Again, it reduces order cycle time and it benefits affects all supply chain partners.…”
Section: Supply Chain Visibility and Supply Chain Performancementioning
confidence: 99%
See 2 more Smart Citations
“…They defined SCP as the benefits an organization gets from supply chain participation of course not limited to efficiency improvement, price reduction, as well as enhancement in cycle time (Yu, 2015). Asnordin et al (2021) observed that previous research has actually confirmed that an effective and reliable supply chain supplies top quality products on time and in the right amounts. Again, it reduces order cycle time and it benefits affects all supply chain partners.…”
Section: Supply Chain Visibility and Supply Chain Performancementioning
confidence: 99%
“…Again, it reduces order cycle time and it benefits affects all supply chain partners. Asnordin et al (2021) asserted that dimension of performance can be defined in various aspects, of course depending on the technique and the factor for determining that dimension of performance. Wood, Reiners, & Srivastava (2017) therefore explained efficiency measurement as the method of examining an individual or multiple tasks in an effective and efficient manner.…”
Section: Supply Chain Visibility and Supply Chain Performancementioning
confidence: 99%
See 1 more Smart Citation
“…, 2018). These digital initiatives include electronic customer service management, blockchain, cloud computing, enterprise planning system and augmenting online order procurement and placement (Asnordin et al. , 2021; Sanders and Morgan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Companies have accelerated their supply chain interactions with the help of digitisation and the introduction of new technologies to drive effective decision-making in the complex and challenging process (Eshkenazi, 2018;Laaper et al, 2018). These digital initiatives include electronic customer service management, blockchain, cloud computing, enterprise planning system and augmenting online order procurement and placement (Asnordin et al, 2021;Sanders and Morgan, 2020). Such novel technologies and analytical methods in supply chain management aided in building competitive advantage and enabled the supply chain operations to boost (Buntz, 2017;Newman, 2018;Vollmer, 2018).…”
Section: Introductionmentioning
confidence: 99%